(untitled) (Journal of Pharmaceutical Negative Results, 2022)
An autoimmune condition known as Alopecia areata (AA) affects the hair follicles and causes patches of noncicatricial hairloss in any area of the body with hair. The purpose of this research was to assess the presence of CD4+,CD39+, FOXP3+Treg cells in patients with Alopecia areata in Iraq. This investigation was conducted at a private dermatological clinic. 45clinically diagnosed patients and 45 healthy controls from various regions of Iraq were included in the case study. Their agesranged from 5 to 59. Using ELISA, CD4+, CD39+, and FOXP3+ were measured. The results indicated a high number ofmale patients in the age range of 21 to 30 years (33.3%) and a high percentage of female patients in the age group of 10 to 20years (30.3%), with no significant levels P> 0.05. When compared to the control group, the concentration of CD4+,CD39+,and FOXP3+ in Alopecia patients was significantly higher than in healthy individuals (P< 0.05). According to this study'sfindings, patients with AA had higher levels of CD4+, CD39+, and FOXP3+ in their blood.